The Analysis of Reflective Learning Toward The Development of Students’ Attitude - Cristianti, Maria Imaculata Indah; Budi Utomo, Cahyo; Murwatiningsi, Murwatiningsi (Educational Management, 2020)
Reflective learning which is applied in SMP Kolese Kanisius Jakarta becomes the uniqueness which is integrated into the school curriculum. The objective of this study is to discover the meaning of reflection learning toward students’ attitude through the structured interview within 3 groups of subject namely students, teachers and parents. The researcher found how the reflective learning has an impact to the development of students’ attitude. As a result, reflective learning has good impact on the development of students’ attitude, independence, and responsibilities which can be seen from the students’ and parents’ point of view. The teachers also get good input to increase how the teachers facilitate the students appropriately. Suitable companion from teachers and parental support are the key to success reflective learning in this school.